Endovascular treatment of a patient with false aneurysm of splenic artery and sharp tortuosity of the arterial flow - S.V. Vereshchagin; A.V. Abramenko; O.A. Khomyachuk; K.S. Rosнchina; O.S. Chernyak (Ендоваскулярна нейрорентгенохірургія, 2020)
A case of endovascular treatment of a patient with a large false aneurysm of the splenic artery resulting from arrosion of its wall into the cavity of a previously existing pancreatic pseudocyst is described. In addition to the rather rare occurrence of this pathology, a feature of this clinical case was the patient’s sharp tortuosity of the access vessels, including the iliac arteries, abdominal aorta, and the splenic artery. Thus, both the endovascular prosthetics of the affected splenic artery and its embolization according to the traditional method using standard angiographic catheters and Gianturco coils turned out to be technically impossible because of the inability to reach the lesion site, especially with access through the common femoral artery that typical for such interventions, which was used by us when performing diagnostic selective arteriography. The second stage was the embolization of the splenic artery by access through the left axillary artery by means of conducting of guiding catheter into the celiac trunk. Through the lumen of this catheter, we introduced a microcatheter, through which detachable microcoils (usually used in interventional neuroradiology) were introduced into the splenic artery proximal and distal to the aneurysm cavity. As a result, the affected area of ​​the splenic artery with aneurysm was completely turned off from the bloodstream and thrombosed, that allowed to avoid extremely risky open surgical intervention and eliminated the risk of rupture of the aneurysm. Medication support included hypotensive therapy to reduce the risk of rupture of the aneurysm (before and after surgery), analgesics for the relief of post-embolization pain, and antibiotics for the prevention of infectious complications associated with pancreatitis and the possible development of spleen infarction. Monitoring the effectiveness of the intervention in the postoperative period was carried out using ultrasound dopplerography.